Preparation, Characterization, Antibacterial Study, Toxicity Study of New Phenylene diamine- Formazan Derivatives - Hussein Ali Ahmed; Nagham Mahmood Aljamali (Institute of Medico-legal Publications Pvt Ltd, 2021)
Formazans are known to be characterized by containing very effective functional groups that have an effecton the possession of any compound with a pharmaceutical and biological characteristic as antimicrobialsfor many microbes, as these compounds have proven high resistance to the spread of cancerous tumors andthe spread of bacteria and fungi. Series of formazan derivatives were synthesized in this study from metaphenylene diamine via imination reaction then coupling reaction to yield new five derivatives. The formattedformazan derivatives have been investigated through various instrumental -spectral techniques representedby (I.R- Infrared spectra ,H. NMR -Proton magnetic resonance , Mass -Spectra )– as a spectrophotometricmeasurements ,then bio- studying via various bio- experiments in this field like cytotoxicity, resistance ofanti-bacteria.